2023
DOI: 10.1200/jco.22.01637
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mediators of Oxaliplatin-Induced Peripheral Neuropathy From Adjuvant Therapy in Stage III Colon Cancer: Findings From CALGB (Alliance)/SWOG 80702

Abstract: PURPOSE We sought to evaluate the independent and interactive associations of planned treatment duration, celecoxib use, physical activity, body mass index (BMI), diabetes mellitus, and vitamin B6 with oxaliplatin-induced peripheral neuropathy (OIPN) among patients with stage III colon cancer enrolled in a clinical trial. METHODS We conducted a prospective, observational study of 2,450 patients with stage III colon cancer enrolled in the CALGB/SWOG 80702 trial, randomly assigned to 6 versus 12 cycles of adjuva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
3
2
Order By: Relevance
“…Obesity was previously shown to be a significant predictor of CIPN severity. 46 , 47 However, in our study we did not find BMI-related differences in CIPN.…”
Section: Discussioncontrasting
confidence: 85%
“…Obesity was previously shown to be a significant predictor of CIPN severity. 46 , 47 However, in our study we did not find BMI-related differences in CIPN.…”
Section: Discussioncontrasting
confidence: 85%
“…DM, hyperglycemia, and other metabolic complications might also lead to cardiovascular disorders and chronic peripheral neuropathy. 12 – 14 , 16 However, we did not find any difference in our analysis ( Figure 3 ). In the current study, the patients with DM and other metabolic syndromes, such as hyperuricemia and hyperlipidemia, were not associated with higher risks of oxaliplatin-associated severe shock.…”
Section: Discussioncontrasting
confidence: 60%
“… 8 , 11 , 27 Cumulative dose of oxaliplatin enhances chronic OIPN. 9 , 16 , 28 , 29 The mechanisms of OIPN include neuron-cell nucleotide damage, mitochondrial breakdown with oxidative stress overload, glial activation, and neuroinflammation. 8 Previous studies showed that oxaliplatin accumulated in the DRG and destroyed neuronal mitochondria by forming platinum–mitochondria DNA adducts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that acute sensory symptoms and chronic sensory neuropathy caused by oxaliplatin usually occurred after cumulative doses of 550 mg/m 2 , which was equivalent to six to seven cycles (3 months) at a dose of 85 mg/m 2 every 2 weeks ( Park et al, 2013 ). In a clinical trial of 2,450 patients with stage III colon cancer recruited from the United States and Canada, patients accepted 12 cycles (6 months) of adjuvant oxaliplatin, fluorouracil, and leucovorin, relative to 6 cycles (3 months), were more likely to experience higher-grade neuropathy and longer times to resolution ( Lee et al, 2023 ). Moreover, similar results have also been obtained in another randomized phase III trial conducted in Japan.…”
Section: Discussionmentioning
confidence: 99%